Using Twitter (X) to Improve Students’ Ability in Writing Analytical Exposition Text - Buono, Ayu Pramesti; Solusia, Carbiriena (Journal of English Language Teaching, 2025)
This study investigates the effectiveness of utilizing Twitter (now X) as a digital platform to enhance students’ skills in writing analytical exposition texts. The research was carried out at SMAN 4 Payakumbuh and employed a quantitative pre-experimental approach, specifically using a one-group pre-test and post-test design. The participants consisted of 24 students from the eleventh grade. The core objective of the study was to determine whether there was a statistically significant difference in the students’ writing performance before and after the implementation of Twitter as a learning tool. Throughout a six-week intervention period, Twitter was actively incorporated into the learning process. During this time, students were exposed to various educational activities on the platform, including engaging with relevant posts, taking part in online discussions, and exploring structured Twitter threads that focused on the features and structure of analytical exposition texts. These interactive and social media-based methods aimed to create a more dynamic and accessible learning environment. The findings indicated a marked improvement in students’ writing abilities. The average score increased from 46 on the pre-test to 79 on the post-test. Furthermore, statistical analysis confirmed that the difference in scores was significant, demonstrating that the use of Twitter as a learning medium positively impacted students’ ability to construct analytical exposition texts.